Sicca manifestations and lymphoproliferation in hepatitis C virus: effects of direct acting antiviral therapy on dryness and B-cell activity compared to Sjögren’s disease - Amina Maher; Mohamed Tharwat Hegazy; Tareq M. Algarf; Manar A. Abdul-Aziz; Luca Quartuccio; Naguib Zoheir; Salvatore De Vita; Gaafar Ragab (Arthritis Research & Therapy)
Abstract Objectives Hepatitis C virus (HCV) can be associated with sicca manifestations. To study the effect of direct-acting antivirals (DAAs) on sicca manifestations in HCV-infected patients and the difference between those patients and others with HCV without dryness & Sjögren’s disease (SjD). Methods We studied 60 patients in 3 groups: Group 1 (20 HCV + sicca), group 2 (20 HCV without sicca), and group 3 (20 SjD). Groups 1 and 2 received DAAs according to the Egyptian Ministry of Health protocols and were evaluated before and after treatment. Group 3 was evaluated once. Our study evaluated the patients by both subjective and objective methods. Results All HCV cases had sustained viral response (SVR). Comparing the characteristics of groups 1 (before treatment) & 3: Group 1 had a higher frequency of RF, cryoglobulins, and polyclonal-hypergammaglobulinemia (P-values 0.021, 0.003, and ˂0.001 respectively). Group 3 had higher scores of VAS dry eye, VAS dry mouth, VAS fatigue, and VAS pain than group 1 (P-values ˂0.001 in all). Group 3 also had a higher frequency of Anti-Ro and Anti-La (P-values < 0.001). Group-1 before DAAs treatment had higher markers denoting B-cell hyperactivity [higher Rheumatoid factor (RF), cryoglobulins, and beta2-microglobulins (β2M)] compared to group-2 which improved markedly after SVR. This supports that group 1 is further ahead in the direction of lymphoproliferation. Group 1 patients after SVR showed marked improvement in VAS dry eye, VAS dry mouth, VAS fatigue, VAS pain, ESSPRI, and ESSDAI (P-values ˂0.003, ˂0.002, ˂0.016, ˂0.001, ˂0.002, and ˂0.014 respectively). There was a significant improvement in RF, and serum β2M levels (after SVR), (P-values ˂0.013, and 0.001 respectively). Group 1 is further ahead in the direction of lymphoproliferation than group 2 with higher statistically significant serum β2M and polyclonal serum protein electrophoresis (P-values 0.006 and 0.047 respectively). Conclusion HCV patients with sicca manifestations treated by DAAs showed significant clinical and immunological improvements. The difference between group 1 (before and after SVR) and group 3 supports the notion that they are two different entities, with different characteristic features. Sicca manifestations improved after the eradication of HCV.